A Five-Component Biginelli-Diels-Alder Cascade Reaction - Maskrey, Taber S.; Frischling, Madeline C.; Rice, Mikhaila L.; Wipf, Peter (Frontiers in Chemistry, 2018)
A new multi-component condensation was discovered during the reaction of a urea, β-keto ester, and formaldehyde. In the presence of catalytic indium bromide, a Biginelli dihydropyrimidinone intermediate was further converted to a five-component condensation product through a formal hetero Diels-Alder reaction. The product structure was confirmed by NMR and NOE analysis, and the proposed stepwise mechanism was supported by the reaction of the Biginelli intermediate with ethyl 2-methylene-3-oxobutanoate.